Government Transfers to Parents and Population Policy in a Global Perspective: An Economic Demographic Perspective. Issue 9 (2nd September 2021) - Kolk, Martin
Abstract: The world is rapidly converging towards lower fertility: in 2020, countries with a total fertility rate of less than 2.25 will encompass more than three-quarters of the world population. This implies that the determinants of childbearing will be increasingly similar in high-income and middle-income regions of the world. In this article, I discuss economic demography in relation to levels of childbearing. How do different societies distribute resources across the life course and between generations, and to what extent is this done through governmental transfers? The extent of such transfers varies considerably between low-income, middle-income, and high-income countries, which I explored through data from the National Transfers Account project. I argue that in low-fertility societies, the extent to which the costs of childrearing are socialised is important for fertility. The extent to which childrearing is socialised will be an important determinant of future fertility levels and, if used as a population policy, offers a straightforward pathway to achieve a desirable population size. As the global fertility decline continues, such policies will be relevant to most societies and a tool for governments to affect fertility levels across many contexts.